2012
DOI: 10.1111/j.1365-2249.2011.04552.x
|View full text |Cite
|
Sign up to set email alerts
|

Control ofMycobacterium tuberculosisgrowth by activated natural killer cells

Abstract: SummaryWe characterized the underlying mechanisms by which glutathione (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 23 publications
1
91
0
3
Order By: Relevance
“…Interestingly, it has been reported that NK cells can contribute to immune defence against MTB through the production of IL-22, which inhibits intracellular mycobacterial growth by enhancing phagolysosomal fusion [51]. A role for glutathione, alone and in conjunction with IL-2 and IL-12, in activating the ability of NK cells to control the growth of MTB inside human monocytes has also been demonstrated [52], highlighting that multiple mechanisms might be involved in restricting MTB intracellular growth by human NK cells. …”
Section: Nk Cells and Tb: In Vitro Studiesmentioning
confidence: 99%
“…Interestingly, it has been reported that NK cells can contribute to immune defence against MTB through the production of IL-22, which inhibits intracellular mycobacterial growth by enhancing phagolysosomal fusion [51]. A role for glutathione, alone and in conjunction with IL-2 and IL-12, in activating the ability of NK cells to control the growth of MTB inside human monocytes has also been demonstrated [52], highlighting that multiple mechanisms might be involved in restricting MTB intracellular growth by human NK cells. …”
Section: Nk Cells and Tb: In Vitro Studiesmentioning
confidence: 99%
“…43 Interestingly, Guerra et al demonstrated that IL12-mediated upregulation of FasL and CD40L was involved in the control of mycobacterium tuberculosis growth by activated NK cells. 44 Deficiency in both IL12 and FasL expression can, therefore, contribute to susceptibility to infection. Previous analysis of patients with IL12RB1 mutations demonstrated deficient IL12/JAK/STAT signaling (as could be confirmed for the patient analyzed here), lack of resulting IFNg production by T and NK cells as well as deficient IL23 signaling and low levels of IL17-producing T cells.…”
mentioning
confidence: 99%
“…Moreover, a direct link between NK cells and MTB-infected cells has been shown to be mediated by the interaction of NKp46 and NKG2D activating receptors on NK cells with infected monocytes [14]. Evidence for NK-mediated control of MTB replication is provided by in vitro experiments in which cells from healthy donors promote intracellular killing of mycobacteria [15][16][17] and lyse monocytes infected with MTB, BCG or M. aviumcomplex [18][19][20]. In addition, NK cells from patients with latent TB contribute to adaptive immunity against MTB by enhancing the mycobacteria-specific CD8 + T cell effector functions [4] and by inhibiting expansion of regulatory T cells [21].…”
Section: Introductionmentioning
confidence: 99%